Entrepreneurship and Innovation in Emerging Economies: Challenges and Opportunities for Sustainable Business Development (Al-Aasar, 2024)
Entrepreneurship and innovation are crucial drivers of economic development, particularly in emerging economies. These regions face unique challenges such as limited access to capital, infrastructure deficits, and regulatory hurdles. However, they also present significant opportunities for sustainable business development through innovation. This paper explores the role of entrepreneurship in fostering economic growth and sustainability in emerging economies, examining both the challenges and the opportunities. It highlights how innovative business models, technological advancements, and policy reforms can facilitate the establishment and growth of sustainable enterprises. Furthermore, the study emphasizes the importance of fostering an entrepreneurial ecosystem that supports creative solutions to pressing social, economic, and environmental issues. The paper concludes with recommendations for entrepreneurs, policymakers, and institutions to leverage the full potential of innovation for sustainable business  practices in emerging markets.